High efficiency protocol for platelet derived fibrin gel loaded with mesenchymal stromal cells extracellular vesicles - Enrico Ragni; Paola De Luca; Simona Landoni; Federico Valli; Leonardo Mortati; Silvia Palombella; Giuseppe Talò; Matteo Moretti; Laura de Girolamo (Regenerative Therapy)
Introduction: Extracellular vesicles from mesenchymal stromal cells (MSC-EVs) are potent stimulators of naïve cartilage and their injection is studied in clinical trials for cartilage lesions, since often cartilage repaired with conventional approaches is incomplete or less performant leading to joint degeneration. The main pitfall of these innovative approaches is the high EVs dispersion into the joint cavity and consequent low concentration at lesion site. Thus, biological scaffolds for concentration of EVs where needed might be a promising option. This work aimed at producing an enhanced platelet-derived fibrin gel loaded with adipose-derived MSCs (ASCs)-EVs. Methods: EVs’ embedment efficiency in platelet gel, their release and incorporation in OA chondrocytes and cartilage explants were monitored by flow cytometry, microfluidic approaches, scansion electron microscopy and real-time quantitative multimodal nonlinear optics imaging. The effect of released EVs was tested in OA chondrocytes by gene expression studies. Results: A protocol ensuring high incorporation EVs efficiency in platelet gels was defined, relying on a one-step modification of the standard procedure used in current clinical practice. Trapped EVs were released continuously for up to 4 weeks and uptaken in pathologic chondrocytes and cartilage explants. The release of the EVs-loaded platelet gel had stronger and synergic anti-inflammatory/matrix remodelling effects with respect to both EVs per se and unloaded gel released products. Conclusions: These results suggest the feasibility of producing a platelet gel loaded with MSC-EVs at high efficiency that can be used as an enhanced tool to foster chondrocyte homeostasis, a key requisite for proper cartilage healing.